Early cognitive and psychological symptoms in cardiac arrest survivors and mental health outcomes among relatives: findings from the REVIVAL cohort - Camilla Dichman; Anne Vinggaard Christensen; Selina Kikkenborg Berg; Dea Siggaard Stenbæk; Bo Gregers Winkel; Britt Borregaard; Jesper Kjaergaard; Mette Kirstine Wagner (Resuscitation Plus)
Aim: To investigate whether early cognitive impairment and symptoms of traumatic distress, anxiety, and depression in out-of-hospital cardiac arrest (OHCA) survivors are associated with clinical symptoms of psychopathology in relatives at follow-up. Methods: This study is a predefined analysis of a multicenter cohort study of OHCA survivors and relatives that took place from January 2018 to February 2022 at three cardiac arrest centers. Applying the Montreal Cognitive Assessment (MoCA), the Impact of Event Scale-Revised (IES-R), and the Hospital Anxiety and Depression Scale (HADS), cognition and symptoms of psychopathology were assessed in survivors during hospitalisation. At three-month follow-up, we evaluated clinical symptoms of post-traumatic stress disorder (PTSD) using IES-R, and clinical symptoms of anxiety and depression with HADS in relatives. Logistic regression models were applied. Results: At follow-up, 146 relatives (84% females) from 297 OHCA survivors participated. Median age was 55 years (IQR 21–79 years). Overall, relatives were found with clinical symptoms of PTSD (25%), anxiety (27%), and depression (14%). In unadjusted analysis, early cognitive impairment (MoCA score < 26) in survivors was associated with higher odds of clinical symptoms of PTSD in relatives (OR (95% CI) 2.61 (1.09–6.24, p = 0.03) at three-months follow-up. This association was no longer significant after adjusting for age. Conclusion: Clinical symptoms of PTSD and anxiety were common in relatives of survivors at three months post-cardiac arrest. Further research is needed to identify factors that may be associated with mental health challenges in relatives to support these families early in the cardiac arrest survivorship.